2014
DOI: 10.1097/md.0000000000000198
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant FOLFIRINOX Application in Borderline Resectable Pancreatic Adenocarcinoma

Abstract: Abstract5-Fluorouracile, oxaliplatin, irinotecan, and leucovorin (FOLFIRINOX) has not been extensively used in the neoadjuvant setting because of concerns with safety and toxicity. We evaluated our institutional experience with neoadjuvant FOLFIRINOX in borderline resectable pancreatic adenocarcinoma (BRPAC). The primary endpoints were completion of therapy to surgery and negative resection margin (R0) rate.Patients with BRPAC treated with neoadjuvant FOLFIRINOX were retrospectively analyzed. Between August 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 17 publications
0
40
0
2
Order By: Relevance
“…FOLFIRINOX regimen resulted in a statistically significant increase in OS (11.1 vs. 6.8 months; P<0.001) and RR (31.6 vs. 9.4%; P<0.001) compared with the results observed with gemcitabine in patients with metastatic disease (6). Thus, FOLFIRINOX has been incorporated in neoadjuvant trials for BRPAC and LAPAC (Table I), either alone or in combination with chemoradiation (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…FOLFIRINOX regimen resulted in a statistically significant increase in OS (11.1 vs. 6.8 months; P<0.001) and RR (31.6 vs. 9.4%; P<0.001) compared with the results observed with gemcitabine in patients with metastatic disease (6). Thus, FOLFIRINOX has been incorporated in neoadjuvant trials for BRPAC and LAPAC (Table I), either alone or in combination with chemoradiation (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the experience in the metastatic setting, many institutions started to recommend the neoadjuvant administration of FOLFIRINOX for patients who were borderline resectable, or locally advanced unresectable. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Since the ACCORD trial was published in 2011, many retrospective studies have confirmed encouraging results for FOLFIRINOX as induction therapy for patients with initially locally advanced PDAC. 9,11 R0 resections are achieved in 40 % of patients with initially borderline/unresectable PDAC.…”
mentioning
confidence: 98%
“…Recently, a number of studies have reported the results of treatment using neoadjuvant FOLFIRINOX, an exceedingly promising chemotherapy regimen. 40,41 Ferrone et al reported outstanding short-term outcomes in patients with BR and locally advanced PDAC. The efficacy of neoadjuvant FOLFIR-INOX was found to be potentially superior to that in the current study with a remarkable decrease in pre-and posttreatment median CA19-9 level from 169 to 0.17 U/mL and a resection rate of 100%.…”
Section: Discussionmentioning
confidence: 99%